The Routledge handbook of policy styles - Howlett, Michael; Tosun, Jale (Routledge, 2021)
Studying policy styles at the national level and beyond / Michael Howlett and Jale Tosun -- National policy styles in theory and practice / Michael Howlett and Jale Tosun -- Adversarial legalism and the American style of policymaking / Jeb Barnes -- Experimentalism as a policy style : the case of China / Jiwei Qian -- From the 'rationalist consensus' to 'exclusive incrementalism' : the 'new' German policy style / Reimut Zohlnhöfer and Jale Tosun -- Authoritarism as a policy style / Aziz Burkhanov -- The concept of a sectoral policy style / Paul Cairney -- Three worlds of social policy styles : lasting legacies or a thing of the past? / Alexander Horn and Jennifer Shore -- Policy styles in healthcare : understanding variations in health systems / Azad Singh Bali and Adam Hannah -- Operationalising and explaining environmental policy styles / Jale Tosun and Marc Debus -- Finance and monetary policy styles / Caner Bakir and M. Kerem Coban -- The concept of administrative styles / Louisa Bayerlein, Christoph Knill and Dionys Zink -- The styles of civil service systems / John Halligan -- Empirically assessing administrative styles as bureaucratic routines / Louisa Bayerlein, Christoph Knill, Yves Steinebach and Dionys Zink -- Convergence in administrative implementation styles in the European Union? / Mark Wiering and Tetty Havinga -- Governance styles : re-thinking governance and public policy / Michael Howlett, Giliberto Capano and M. Ramesh -- Media-driven agenda-setting styles / Max Grömping -- Interest groups and agenda setting styles / Darren R. Halpin and Bert Fraussen -- The politics of parliamentary agenda-setting styles / Shaun Bevan, Enrico Borghetto and Henrik Seeberg -- Policy formulation styles : policy design and non-design / Michael Howlett and Ishani Mukherjee -- Policy over- and underreaction as policy style / Moshe Maor -- Styles of policy advice : a typology for comparing the standard operating procedures for the provision of policy advice / David Aubin and Marleen Brans -- Executive policy styles / Christopher A. Cooper and Patrik Marier -- Leaders' and managers' decision-making styles / Maria Tullia Galanti -- Varieties of executive styles / Kai Wegrich -- Instruments and implementation styles / Michael Howlett, Anthony Perl and M. Ramesh -- Regulatory styles and their implications / Christian Adam and Steffen Hurka -- Implementation style dynamics : changing patterns of instrument choice over time? / Michael Howlett -- When policy learning meets policy styles / Claire A. Dunlop and Claudio M. Radaelli -- Participatory vs expert evaluation styles / Fritz Sager and Céline Mavrot -- Policy evaluation styles / Fabrizio De Francesco and Valérie Pattyn -- Institutional and process dimensions of policy styles : key insights / Michael Howlett and Jale Tosun.
Includes bibliographical references and index
Keywords: Electronic books; Politischer Prozess; Staatstätigkeit; Politischer Stil